A checklist of reptilian fauna of Visakhapatnam district (Zoological Records and Reviews, 2021)
Visakhapatnam district, situated in the northern Eastern Ghats of Andhra Pradesh, India, encompasses a highlyheterogeneous landscape including coastal mangroves, hill forests, riverine corridors, scrub woodland, and urban andperi-urban habitats. Despite this ecological diversity, no comprehensive, verified checklist of the reptilian fauna of thedistrict has previously been published. This study presents a systematically compiled checklist of reptiles fromVisakhapatnam district based on field surveys at 62 localities conducted between 2017 and 2020, supplemented byverified museum records from the Zoological Survey of India and the Natural History Museum London. A total of 94reptile species are confirmed for the district, comprising 3 crocodilians, 18 chelonians, 38 lizards, and 35 snakes across26 families. Fourteen species are recorded for the first time from Visakhapatnam district, and four represent new recordsfor Andhra Pradesh. Twenty-two species are listed under CITES Appendices I or II, and 11 species are assessed asThreatened under IUCN criteria. The checklist is annotated with habitat associations, conservation status, and notes ondistributional range for each species. Key diversity hotspots are identified as the Nagarjunasagar-Srisailam TigerReserve buffer forests, the Coringa Mangrove Wildlife Sanctuary, and the Araku Valley tribal uplands. Conservationchallenges including road mortality, illegal wildlife trade, and habitat fragmentation are discussed with reference toevidence gathered during the survey.
Keywords: conservation; CITES; IUCN; biodiversity; herpetofauna; Andhra Pradesh; checklist; Eastern Ghats; Visakhapatnam; reptiles